5
$\begingroup$

Title says it all, I just want to know how to factor $(x+y)^4+x^4+y^4$. I only know that it's possible to factor, but got no idea how to do it. If it were a single-variable polynomial I could try to find rational roots or something, but I'm lost with this one.

$\endgroup$
  • $\begingroup$ $2x^4 + 4x^3y + 6x^2y^2 + 4^xy^3 + 2y^4$ can be split up as $(2x^4 + 2x^3y + 2x^2y^2) + (2x^3y + 2x^2y^2 + 2xy^3) + (2x^2y^2 + 2xy^3 + 2y^4)$, or $2(x^2 + xy + y^2)^2$. $\endgroup$ – Chris Mar 7 '17 at 20:40
1
$\begingroup$

Beyond what I have posted, it cannot be factored in the real field. If you want to factor it in the complex field, you have to learn how to solve a quartic equation because you essentially need to know that roots of $(t+1)^4 + t^4 + 1 = 2t^4 + 4t^3 + 6t^2 + 4t + 2 = 0$, it can be simplified to $t^4 + 2t^3 + 3t^2 + 2t + 1 = 0$.Lucky enough, this is equal to $(t^2 + t + 1)^2$

Thus $x^4 + y^4 + (x + y)^4 = (x^2 + xy + y^2)^2$. No further factorization is available in the real field...

Best wishes

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ Are you sure about the last line? The coefficient of $x^4$ on the LHS is 2, but the coefficient of $x^4$ on the RHS is 1. Moreover, plugging in $x=1$, $y=0$, we get that LHS = 2, but RHS = 1. What I'm trying to say is, there is clearly something wrong with your last line... [Figured it out - you are missing a '2' in front of the brackets on the RHS of the last equality - I am not being allowed to edit your answer for some reason] $\endgroup$ – John Don Mar 7 '17 at 21:13
3
$\begingroup$

Note that $$(x+y)^4 + x^4 + y^4 = y^4 ((x/y+1)^4 + (x/y)^4 + 1)$$ and see if you can factor $((t+1)^4 + t^4 + 1$. There is a quadratic factor.

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ Just a quick question, did you do this manipulation just so you can have it in one variable? When factoring, is it always best to try to reduce it to one variable? $\endgroup$ – Ovi Mar 7 '17 at 20:43
  • $\begingroup$ This answer seems the most informative and straightforward for the OP - it gives a good general method for factoring polynomials in two variables by reducing it to something in one variable. $\endgroup$ – John Don Mar 7 '17 at 21:19
  • $\begingroup$ This works when a two-variable polynomial is homogeneous. In general, things are more complicated. $\endgroup$ – Robert Israel Mar 8 '17 at 0:56
  • $\begingroup$ @RobertIsrael Ah yes, I didn't mean to be quite so general, but yes, it is a nice reliable method of factoring homogeneous two variable polynomials, which is accessible to those who have not come across many polynomials in more than one variable before. $\endgroup$ – John Don Mar 8 '17 at 19:52
1
$\begingroup$

I know that using complex algebra, we can factor $x^4 + y^4 = (x^2 + y^2 + \sqrt{2}xy)(x^2 + y^2 - \sqrt{2}xy)$. I have no idea how to proceed forward... Good luck

| cite | improve this answer | |
$\endgroup$
1
$\begingroup$

I am sorry, there is a slight mistake, I forgot factoring 2. Thus $x^4 + y^4 + (x+y)^4 = 2(x^2 + xy + y^2)^2$

| cite | improve this answer | |
$\endgroup$
1
$\begingroup$

This is a symmetric polynomial in $x$ and $y$, hence it can be expressed, by Newton's theorem, as a polynomial in $s=x+y$ and $p=xy$.

Indeed $x^2+y^2=(x+y)^2-2xy=s^2-2p$, whence $$x^4+y^4=(x^2+y^2)^2-2x^2y^2=(s^2-2p)^2-2p^2=s^4-4ps^2+2p^2.$$ Therefore $$(x+y)^4+x^4+y^4=2s^4-4ps^2+2p^2=2(s^2-p)^2=2(x^2+xy+y^2)^2.$$

$x2+xy+y^2$ is irreducible in $\mathbf R[x]$, but fractors in $\mathbf C[x]$ as $$(x-jy)(x-j^y),\quad\text{where } j\; \text{and }j^2 \;\text{are the non-real cubic roots of unity.}$$

| cite | improve this answer | |
$\endgroup$
0
$\begingroup$

$$(x+y)^4+x^4+y^4=(x^2+y^2+2xy)^2+(x^2+y^2)^2-2(xy)^2=\\ [(x^2+y^2+2xy)^2-(xy)^2]+[(x^2+y^2)^2-(xy)^2]=\\ (x^2+y^2+xy)(x^2+y^2+3xy)+(x^2+y^2+xy)(x^2+y^2-xy)=\\ (x^2+y^2+xy)(2x^2+2y^2+2xy)=2(x^2+y^2+xy)^2$$

| cite | improve this answer | |
$\endgroup$
0
$\begingroup$

$$x^4 + y^4 + (x + y)^4 =2 x^4 + 4 x^3 y + 6 x^2 y^2 + 4 x y^3 + 2 y^4$$ $$=x (x (x (2 x + 4 y) + 6 y^2) + 4 y^3) + 2 y^4 =2 x^4 + y (4 x^3 + y (6 x^2 + y (4 x + 2 y)))$$ $$=4 y^2 (x^2 + x y) + 2 (x^2 + x y)^2 + 2 y^4 =2 (x^4 + 2 x^3 y + 3 x^2 y^2 + 2 x y^3 + y^4)$$ $$=2 (x^2 + x y + y^2)^2$$

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.